ACR Appropriateness Criteria® Antenatal Hydronephrosis-Infant - Brown, Brandon P; Simoneaux, Stephen F; Dillman, Jonathan R; Rigsby, Cynthia K; Iyer, Ramesh S; Alazraki, Adina L; Bardo, Dianna M E; Chan, Sherwin S; Chandra, Tushar; Dorfman, Scott R; Garber, Matthew D; Moore, Michael M; et al. (Journal of the American College of Radiology, 2020)
Antenatal hydronephrosis is the most frequent urinary tract anomaly detected on prenatal ultrasonography. It occurs approximately twice as often in males as in females. Most antenatal hydronephrosis is transient with little long-term significance, and few children with antenatal hydronephrosis will have significant obstruction, develop symptoms or complications, and require surgery. Some children will be diagnosed with more serious conditions, such as posterior urethral valves. Early detection of obstructive uropathy is necessary to mitigate the potential morbidity from loss of renal function. Imaging is an integral part of screening, diagnosis, and monitoring of children with antenatal hydronephrosis. Optimal timing and appropriate use of imaging can reduce the incidence of late diagnoses and prevent renal scarring and other complications. In general, follow-up neonatal ultrasound is recommended for all cases of antenatal hydronephrosis, while further imaging, including voiding cystourethrography and nuclear scintigraphy, is recommended for moderate or severe cases, or when renal parenchymal or bladder wall abnormalities are suspected. The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.